Risk factors and outcomes of chronic opioid use following trauma. Issue 4 (7th February 2020) - von Oelreich, E.; Eriksson, M.; Brattström, O.; Sjölund, K.‐F.; Discacciati, A.; Larsson, E.; Oldner, A.
Abstract : Background: The growing problem of opioid misuse has become a serious crisis in many countries. The role of trauma as a gateway to opioid use is currently not determined. The study was undertaken to assess whether traumatic injury might be associated with chronic opioid use and accompanying increased long‐term mortality. Methods: Injured patients and controls from Sweden were matched for age, sex and municipality. After linkage to Swedish health registers, opioid consumption was assessed before and after trauma. Among injured patients, logistic regression was used to investigate factors associated with chronic opioid use, assessed by at least one written and dispensed prescription in the second quarter after trauma. Cox regression was employed to study excess risk of mortality. In addition, causes of death for postinjury opioid users were explored. Results: Some 13 309 injured patients and 70 621 controls were analysed. Exposure to trauma was independently associated with chronic opioid use (odds ratio 3·28, 95 per cent c.i. 3·02 to 3·55); this use was associated with age, low level of education, somatic co‐morbidity, psychiatric co‐morbidity, pretrauma opioid use and severe injury. The adjusted hazard ratio for death from any cause 6–18 months after trauma for chronic opioid users was 1·82 (95 per cent c.i. 1·34 to 2·48). Findings were similar in a subset of injured patients with no pretrauma opioid exposure. Conclusion: Traumatic injury was associated with chronic opioid use. These patients have an excess risk of death in the 6–18 months after trauma. Abstract : The role of trauma as a gateway to opioid use is currently not determined. In a matched‐cohort study, traumatic injury was associated with chronic opioid use, which was associated with long‐term mortality. The results highlight the risk of chronic opioid use after trauma, as well as the contribution of trauma to the current global opioid crisis. Significant problem. associated with increased mortality Abstract : Antecedentes: El uso indebido de opioides es un problema creciente que se ha convertido en una grave crisis en muchos países. No se ha analizado el papel de las lesiones traumáticas como puerta de entrada al uso de opioides. Se estableció la hipótesis de que una lesión traumática podría asociarse con el uso crónico de opioides y acompañarse de un aumento de la mortalidad a largo plazo. Métodos: Se ajustaron por edad, sexo y municipio a los pacientes suecos con lesiones traumáticas y sus controles. Después de vincular varios registros de salud suecos, se evaluó el consumo de opioides antes y después de la lesión traumática. En los pacientes con lesiones traumáticas, se utilizó una regresión logística para definir los factores asociados con el uso crónico de opioides, definida como una receta prescrita y dispensada en el segundo trimestre después de la lesión traumática, y ​​una regresión de Cox para estudiar el exceso de riesgo de mortalidad. Además, se exploraron las causas de muerte de los usuarios de opioides postraumáticos. Resultados: Se analizaron 13.309 pacientes con lesiones traumáticas y 70.621 controles. La exposición a una lesión traumática se asoció de forma independiente con el uso crónico de opioides, (razón de oportunidades, odds ratio, OR) OR 3, 3 (i.c. del 95% 3, 0‐3, 6), y dicho uso se asoció con la edad, el bajo nivel educativo, las comorbilidad físicas y psiquiátricas, el uso previo de opioides y la gravedad de las lesiones. El cociente de riesgos instantáneos, hazard ratio, HR ajustado de muerte por cualquier causa a los 6‐18 meses de la lesión traumática para los consumidores crónicos de opioides fue de 1, 8 (i.c. del 95% 1, 3‐2, 5). En un subconjunto de pacientes con lesiones traumáticas sin exposición previa a los opioides, los hallazgos fueron similares. Conclusión: La lesión traumática se asoció con el uso crónico de opioides. Estos pacientes presentan un exceso de riesgo de mortalidad entre los 6 y 8 meses después del trauma.